Depletion of Arabidopsis ACYL-COA-BINDING PROTEIN3 Affects Fatty Acid Composition in the Phloem - Hu, Tai-Hua; Lung, Shiu-Cheung; Ye, Zi-Wei; Chye, Mee-Len (Frontiers in Plant Science, 2018)
Oxylipins are crucial components in plant wound responses that are mobilised via the plant vasculature. Previous studies have shown that the overexpression of an Arabidopsis acyl-CoA-binding protein, AtACBP3, led to an accumulation of oxylipin-containing galactolipids, and AtACBP3pro::BETA-GLUCURONIDASE (GUS) was expressed in the phloem of transgenic Arabidopsis. To investigate the role of AtACBP3 in the phloem, reverse transcription−polymerase chain reaction (RT-PCR) and western blot analysis of phloem exudates from the acbp3 mutant and wild type revealed that the AtACBP3 protein, but not its mRNA, was detected in the phloem sap. Furthermore, micrografting demonstrated that AtACBP3 expressed from the 35S promoter was translocated from shoot to root. Subsequently, AtACBP3 was localised to the companion cells, sieve elements and the apoplastic space of phloem tissue by immunogold electron microscopy using anti-AtACBP3 antibodies. AtACBP3pro::GUS was induced locally in Arabidopsis leaves upon wounding, and the expression of wound-responsive jasmonic acid marker genes (JASMONATE ZIM-DOMAIN10, VEGETATIVE STORAGE PROTEIN2 and LIPOXYGENASE2) increased more significantly in both locally-wounded and systemic leaves of the wild type in comparison to acbp3 and AtACBP3-RNAi. Oxylipin-related fatty acid (FA) (C18:2-FA, C18:3-FA and methyl jasmonate) content was observed to be lower in acbp3 and AtACBP3-RNAi than wild-type phloem exudates using gas chromatography−mass spectrometry. Experiments using recombinant AtACBP3 in isothermal titration calorimetry analysis showed that medium- and long-chain acyl-CoA esters bind (His)6-AtACBP3 with KD values in the micromolar range. Taken together, these results suggest that AtACBP3 is likely to be a phloem-mobile protein that affects the free FA pool and jasmonate content in the phloem, possibly by its binding to acyl-CoA esters.